If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -3x(-2) = 0 Reorder the terms for easier multiplication: -4 + -3 * -2x = 0 Multiply -3 * -2 -4 + 6x = 0 Solving -4 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 6x = 0 + 4 6x = 0 + 4 Combine like terms: 0 + 4 = 4 6x = 4 Divide each side by '6'. x = 0.6666666667 Simplifying x = 0.6666666667
| ept=qt | | -2(m+7)=-31 | | c=17cm | | 15+5x+6X=180 | | -y=5-4x | | 3x^2/2 | | -1=-3x+22x | | 4r+2r=-34 | | 6x-9=-4x+3 | | 8x+7-9=90 | | X=2/6=-19/6 | | 2x-1+4=-8 | | 2(m-8)=24 | | x+6=15.2 | | -3y+4x=27 | | 4(2x+4)+5(3x-5)= | | 12(3x+5)-(2+3x)7=346 | | 6x+-5y=16fory | | 4-x(-2)= | | -8n-7+3=15 | | 8+2v=4 | | 13x-3=-11 | | b//8=-3 | | 21=-1.5x | | 112+12m=208 | | 2y+3-y-(-2)= | | 3x-8y=100 | | -2+4=4-3 | | 34=-9+7(b-2) | | 20n-16=304 | | 7(2x+4)=6(2x-3) | | 11w=5940 |